Immunity Response Against Methicillin-Resistant Staph aureus Infection (Literature Review) (Eurasian Journal of Research, Development and Innovation, 2024)
This articles highlight on the role Immunity Response Against Methicillin-Resistant Staph aureus Infection , the study showed that interleukin-6 (IL-6) regulates the immune system and mediates inflammation, This response will give you a rundown of interleukin-6, what it does, and how it's involved in many disorders .while the The chemokine interleukin-8 (IL-8), sometimes called CXCL8, plays a role in controlling immunological responses and inflammation. It is essential for attracting and activating neutrophils to infection and tissue damage sites. Macrophages, endothelial cells, fibroblasts, and epithelial cells all contribute to the production of IL-8 when exposed to pro- inflammatory stimuli such as cytokines, tissue damage, or bacterial or viral infections